The Influence Of Leadership Style, Motivation, Discipline And Workload On Employees’ PerformanceAt The Food Security Service Of Bengkulu Province - Rusminita, Esi; Irwanto, Tito; Hidayah, Nenden Restu (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
Leadership is at the same time a manager who must organize, give orders as well as protect his subordinates, namely employee performance and solve problems that arise. The purpose of thisstudy was to determine the effect of the leadershipstyle of the Head of Service on employee performance at the Food SecurityService of Bengkulu Province. The sample in this study were 50 employees whoworked at the Food Security Service of Bengkulu Province. Data collection using questionnaires and analysis methods used are validity test analysis, reliabilitytest, multiple linear regression, coefficient of determination R2 and hypothesis testing.Based on the results of thestudy, the multiple linear regression equation isY = 2.643 + 0.013X1 + 0.026X2 + 0.268X3 + 0.653X4 + e. Variable X1(Leadership Style) has a significant effect on Y (Employee Performance) this can be seen from the significance value of 0.05 <0.01, it can be concluded that hypothesis 1 is accepted. Variable X2 (Motivation) has a significant effect on Y (Employee Performance) this can be seen from the significance value of 0.05 <0.01, it can be concluded that hypothesis 2 is accepted. Variable X3 (Discipline) has a significant effect on Y (Employee Performance) this can be seen from the significance value of 0.01 <0.05, it can be concluded that hypothesis 3 is accepted. Variable X4 (Workload) has a significant effect on Y (Employee Performance) this can be seen from the significance value of 0.01 <0.05, it can be concluded that hypothesis 4 is accepted. The simultaneous test results show that H0 is rejected and Ha is accepted, between the independent variables, namely X1 (leadership style), X2 (motivation), X3 (discipline), X4 (workload), have a significant effect together on employee performance (Y) because the significant value of 0.01 is less than 0.05.